PENINGKATAN KOMITMEN PROFESIONAL MELALUI PEMBERDAYAAN PSIKOLOGIS DAN KOMPETENSI PROFESIONAL DAN DAMPAKNYA TERHADAP PRESTASI KERJA GURU - Istajib Kulla Himmy; Wuryanti Wuryanti (Jurnal Riset Bisnis Indonesia, 2016)
Teachers have a very strategic position and role in the national development, especially in thefield of education. Teacher’s competence as an educator is very important issue. However, we canfind some teachers that do not reflect its strategic role as a teacher, even he is away from theline of teacher identity, deviations moral, display a personality that is not reasonable, showing aweak religious norms and many other factors. Shortly, it can give bad excesses for education, inparticular to the quality of graduates and the output of education and community character as anobject-driven education teachers. So, the research problem can be formulated as “how is the modelof improvement of professional commitment through psychological empowerment and professionalcompetence of educators and their impact on job performance. Based on hypothesis testing whichhas been filed with the multiple linear regression model with PLS software (Part Least Square), withrespondents as many as 122 people who is a teacher at SMU 4 and SMU 9 Semarang. Results ofthe study are: the higher psychological empowerment will enhance the professional commitment ofteachers, psychological empowerment has no significant effect on the increase in work performanceof teachers, higher professional competence will increase the professional commitment of teachers,higher professional competence will improve on the performance of the teacher, the more highprofessional commitment it will improve on the performance of teachers. Further Researchersadvised to examine the model to the larger scale of respondents so that research results can begeneralized further.Keyword: professional commitment, psychological empowerment, professional competence, jobperformance.